Elevated monocyte-to-high-density lipoprotein ratio is associated with increased risk of cognitive impairment and severe cerebral small vessel disease burden - Zhao, Yueshan; Li, Meixi; Zhang, Juan; Wang, Chao; Zhao, Mengyao; Yang, Qishuo; Wang, Tianjun; Lv, Peiyuan (Frontiers in Aging Neuroscience, 2025)
BackgroundMonocyte-to-high-density lipoprotein ratio (MHR), as a novel biomarker, has shown potential in predicting the onset and progression of various diseases. However, the relationship between MHR and cerebral small vessel disease (CSVD) as well as cognitive impairment (CI), which are inflammation-related conditions remains unclear. This research explores the relationship between MHR and total CSVD burden as well as CI.MethodsThis retrospective analysis included 212 eligible patients. On the basis of Mini-Mental State Examination (MMSE) scores, patients were classified into CI and no CI groups. Total CSVD burden was assessed using a composite score incorporating four MRI-based imaging markers. Participants were further stratified into mild and severe CSVD burden groups. MHR was determined by dividing the blood monocyte count by the high-density lipoprotein (HDL) concentration. Statistical analyses, including logistic regression, trend tests, restricted cubic spline modeling, and mediation analysis, were conducted using SPSS 26.0 and R software to explore the associations of MHR with CI, and CSVD burden.ResultsNon-parametric analysis revealed that patients with CI and those with severe CSVD burden exhibited significantly higher MHR levels (p < 0.05) compared to their respective counterparts. Multivariable logistic regression identified elevated MHR (OR = 1.462, 95%CI: 1.057–2.022, p = 0.022) and severe CSVD burden (OR = 2.456, 95%CI: 1.306–4.617, p = 0.005) as significant risk factors for CI. Additionally, higher MHR levels were independently associated with severe CSVD burden (OR = 1.596, 95%CI: 1.092–2.334, p = 0.016). Compared to the lowest MHR tertile, the highest tertile exhibited a remarkably higher risk of CI (OR = 3.743, 95%CI: 1.557–8.995; Ptrend = 0.010) and severe CSVD burden (OR = 2.594, 95%CI: 1.086–6.195; Ptrend = 0.019). Restricted cubic spline analysis confirmed a non-linear association between MHR and both CI and severe CSVD burden. Mediation analysis further demonstrated that CSVD burden significantly mediated the relationship between MHR and CI.ConclusionElevated MHR is related to increased CSVD burden and CI. The mediating roles of severe CSVD burden indicates that a high MHR level may contribute to the progression of CSVD, thereby elevating the risk of CI.